HIMPUNAN KUBIK ASIKLIK DAN KUBUS DASAR - Wiwi Ulmayani (Jurnal Matematika UNAND, 2013)
Given a topological space X. Then define an algebra object H∗ (X) whichis called the homology group of X. H∗ (X) is the collection the kth homology group ofX which is denoted by Hk(X). An elementary cube Q is a finite product of elementaryintervals I = [l, l + 1] or I = [l, l], for some l ∈ Z. In this paper, it is proved that allelementary cubes are acyclic, which means that Hk(Q) is isomorphic to Z if k = 0, andHk(Q) is isomorphic to 0 if k > 0.